Agriscience : fundamentals & applications - L. DeVere Burton (Thomson/Delmar Learning, 2007)
Agriscience Fundamentals and Applications is the premier introductory textbook for agricultural education in secondary schools. It addresses the entire agricultural industry and introduces science as the basis for higher productivity and for the safest food system in the world. At the same time, the authors introduces agricultural careers and opportunities, the integration of science into the agricultural curriculum, information accessed via the Internet, and National FFA programs related to agriscience and technology.